Real time strategic change : how to involve an entire organization in fast and far-reaching change - Jacobs, Robert W., 1963- (Berrett-Koehler Publishers, 1997)
Real time strategic change is a way of redesigning how organizations change-a mindset and accompanying methodology-that ensures that Change occurs at a fast pace and in real time throughout an organization. Change occurs simultaneously within the whole organization. Buy-in, commitment to, and ownership of a change effort is a natural by-product of involving people in the process of change. People feel responsible for the ultimate success of the organization's change effort.